Effect of High-Pressure Processing on the Microbial Quality throughout the Shelf Life of Vacuum-Packed Sliced Ham and Frankfurters - Botsaris, George; Taki, Anastasia (My University, 2015)
Microbial spoilage is one of the most important factors threatening the shelf life of meat products. High-pressure processing (HPP) is growing out of its infancy with an increasing number of commercial applications. The aim of this study was to evaluate the efficiency of HPP on the microbial quality of commercial ham and frankfurters over their shelf life period. Commercially manufactured ham and frankfurters were processed with HPP at 600MPa for 3min and were then stored in parallel with nontreated samples (control) at 4C for a period of 7 weeks. All samples were weekly analyzed for the following parameters: total aerobic count (TAC), coliforms, Escherichia coli, staphylococci, yeasts and moulds, Salmonella spp., and Listeria spp. At the end of the tested shelf life period, a significant difference (P<0.005) was observed on the TAC between HPP-treated and nontreated samples for both products tested, demonstrating the efficiency of the HPP method. Practical Applications: This study shows that the HPP treatment at 600MPa for 3min is effective at increasing significantly the shelf life of the two products tested. Sliced ham and frankfurters are among the most popular meat products consumed and the majority of the producers apply vacuum packaging to these products. The meat industry is seeking ways to increase the shelf life of these products and it was shown here that this can be achieved by the application of modern commercial HPP systems.
Keywords: Meat-products; Food safety; Spoilage; Beef; Oil